External pressures, managerial motive and corporate sustainability strategy: evidence from a developing economy - Mohamed M. Shamil,; Junaid M. Shaikh,; Ho, Poh-Ling; Anbalagan Krishnan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Based on social-system theories, our study analyzes the (i) influence of institutional and external stakeholder pressure on the adoption of corporate sustainability strategy and (ii) role of managerial motive in mediating the influence of external pressures on the adoption of corporate sustainability strategy. A questionnaire was developed to collect data from listed companies in Sri Lanka, and the data were analyzed using the covariance-based structural equation modeling technique. The results showed that the adoption of corporate sustainability strategy is positively influenced by external stakeholder pressures, whereas institutional pressures had no significant impact. The managerial motive was found to mediate institutional pressures, but it was not to mediate external stakeholder pressure on adopting corporate sustainability strategy. This is the first study from Sri Lanka to investigate the interplay between external forces and managers’ internal motivations concerning adopting corporate sustainability strategy. External stakeholders and the institutional environment can call upon organizations to embrace a sustainability agenda in economies where adopting sustainability is purely voluntary. Managers may absorb the external pressures on sustainability and drive organizations to engage in sustainability initiatives.